PERAN GURU AKIDAH AKHLAK DALAM MENGEMBANGKAN KREATIVITAS PESERTA DIDIK DI MTS AL-MAZAAKHIRAH BARAMULI KABUPATEN PINRANG - Azzam, Risqy Abdullah; Mustamin; Ahmad; Rosmiati; Wahab, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the role of Akidah Akhlak teachers in developing the learning creativity of seventh-grade students at MTs Al-Mazaakhirah Baramuli and to identify the obstacles faced by teachers in the process of developing students’ learning creativity. This research employed a qualitative descriptive method with a qualitative approach. The subjects of this study consisted of the principal, Akidah Akhlak teachers, and seventh-grade students. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis techniques included data collection, data reduction, data presentation, and conclusion drawing. The validity of the data was tested using source triangulation, technique triangulation, and time triangulation. The results of the study showed that Akidah Akhlak teachers play an important role in developing students’ learning creativity through various learning activities, such as assigning handicraft tasks, giving appreciation and suggestions, using video learning media, encouraging students to express opinions, assigning group work, and applying mind mapping methods. These efforts were able to increase students’ activeness, motivation, self-confidence, and creative thinking skills. However, several obstacles were found in the implementation process, including limited learning facilities such as the lack of books or textbooks, low self-confidence among students, lack of courage to try new things, and monotonous learning activities. To overcome these obstacles, teachers attempted to provide motivation, use varied learning methods, and create a comfortable and enjoyable learning atmosphere. Therefore, the role of Akidah Akhlak teachers greatly influences the development of students’ learning creativity.